2017
DOI: 10.5468/ogs.2017.60.5.405
|View full text |Cite
|
Sign up to set email alerts
|

Use of progesterone supplement therapy for prevention of preterm birth: review of literatures

Abstract: Preterm birth (PTB) is one of the most common complications during pregnancy and it primarily accounts for neonatal mortality and numerous morbidities including long-term sequelae including cerebral palsy and developmental disability. The most effective treatment of PTB is prediction and prevention of its risks. Risk factors of PTB include history of PTB, short cervical length (CL), multiple pregnancies, ethnicity, smoking, uterine anomaly and history of curettage or cervical conization. Among these risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 86 publications
2
27
0
Order By: Relevance
“…Currently, progestogen supplement therapy is recommended for women with a history of spontaneous PTB or with short CL by many guidelines, including those of the National Institute for Health and Care Excellence and the American College of Obstetricians and Gynecologists 32–35 . There is no clear consensus on the optimal indication, route of administration or dose among these guidelines, however, because the selection criteria of the study populations and methods of progestogen therapy vary substantially among the available studies 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, progestogen supplement therapy is recommended for women with a history of spontaneous PTB or with short CL by many guidelines, including those of the National Institute for Health and Care Excellence and the American College of Obstetricians and Gynecologists 32–35 . There is no clear consensus on the optimal indication, route of administration or dose among these guidelines, however, because the selection criteria of the study populations and methods of progestogen therapy vary substantially among the available studies 14 …”
Section: Discussionmentioning
confidence: 99%
“…Progestogen supplement therapy is one of the few proven effective methods for preventing PTB in women with a history of spontaneous PTB or with short CL 9–13 . Progestogens are available in natural micronised or synthetic formulations for intramuscular, vaginal (tablet or gel) or oral administration 14 . Previous studies have reported that the injection of 17α‐hydroxyprogesterone caproate (17‐OHPC) can reduce recurrent PTB in women with a previous history of PTB 15–17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, no evidence exists on which progesterone supplementation can maximize the preventative effects while minimizing the side effects. Therefore, further researches are still required to define the optimal type, dose and duration of progesterone depending on various indications of treatment [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the utility of progesterone administration has been extensively studied, in particular for its effect on prolonging pregnancy and thereby ensuring better neonatal outcome. This led to a substantial increase in the use of synthetic and natural progestogens in singleton and twin pregnancies [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%